Modal analysis of fixed-fixed beam - Siti Sarah, Ahmad (2010)
This project work describes in detail, includes a brief description of the Modal Analysis of Fixed-Fixed Beam, supplemented by a good number of necessary and descriptive drawings which makes this project report very easy to understand. The objective of this project is to determine the dynamic behaviour or modal characteristics of fixed-fixed beam using modal analysis. There are two methods used in this project which are simulation by using Algor software and experimental by using Hammer Excitation. In addition to these, the report also contains the details regarding the different type of natural frequencies and mode shapes. In simulation, the natural frequency based on the mesh size starting from 100%,90%,80% and 70%. The result obtained from the minimum value of natural frequency lies between range 113.1345Hz and 160.0712Hz which refer to the Mode 1. Mode 5 of the maximum value of natural frequency is in the range of 640.0954Hz until 713.1101Hz. By comparing with the experimental results, the average of first point is 163Hz and the fifth point is 740.5Hz. Both results show that there are no much different as the errors are between 0.13% until 2.45%. The result from both method can be accepted regarding to the objective achieved.